Metanasi CO2 menggunakan Katalis Ni/Al2O3 dengan Variasi Konsentrasi KOH dan Temperatur - Nanda Putri, Azadia; Robert Junaidi; Cindi Ramayanti (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The transportation sector is one of the largest contributors to greenhouse gas emissions, which play a significant role in global climate change. One preventative measure that can be taken is to convert carbon dioxide (CO₂) into methane (CH₄), known as the CO₂ methanation process. The purpose of this study was to produce methane gas with a higher conversion percentage, as well as to observe the effect of variations in operating temperature and KOH liquid concentration on the methane gas produced. In this study, CO2 was used as the raw material with a Ni/Al2O3 catalyst and zn promoter. The temperature was set at 165°C, 175°C, 185°C, 195°C, and 205°C, with KOH liquid concentrations varying from 4M to 5M. The resulting methane (CH4) gas will be analyzed using a Multi Gas Detector Analyzer.